Decisions on antibiotic prescribing for suspected urinary tract infections in frail older adults: a qualitative study in four European countries. (12th June 2022) - Hartman, Esther A R; Groen, Wim G; Heltveit-Olsen, Silje Rebekka; Lindbæk, Morten; Høye, Sigurd; Sundvall, Pär-Daniel; Skoglund, Ingmarie; Snaebjörnsson Arnljots, Egill; Gunnarsson, Ronny; Kowalczyk, Anna; Godycki-Cwirko, Maciek; Kosiek, Katarzyna; et al.
Abstract: Background: a suspected urinary tract infection (UTI) is the most common reason to prescribe antibiotics in a frail older patient. Frequently, antibiotics are prescribed unnecessarily. To increase appropriate antibiotic use for UTIs through antibiotic stewardship interventions, we need to thoroughly understand the factors that contribute to these prescribing decisions. Objectives: (1) to obtain insight into factors contributing to antibiotic prescribing for suspected UTIs in frail older adults. (2) To develop an overarching model integrating these factors to guide the development of antibiotic stewardship interventions for UTIs in frail older adults. Methods: we conducted an exploratory qualitative study with 61 semi-structured interviews in older adult care settings in Poland, the Netherlands, Norway and Sweden. We interviewed physicians, nursing staff, patients and informal caregivers. Results: participants described a chain of decisions by patients, caregivers and/or nursing staff preceding the ultimate decision to prescribe antibiotics by the physician. We identified five themes of influence: (1) the clinical situation and its complexity within the frail older patient, (2) diagnostic factors, such as asymptomatic bacteriuria, (3) knowledge (gaps) and attitude, (4) communication: interprofessional, and with patients and relatives and (5) context and organisation of care, including factors such as availability of antibiotics (over the counter), antibiotic stewardship efforts and factors concerning out-of-hours care. Conclusions: decision-making on suspected UTIs in frail older adults is a complex, multifactorial process. Due to the diverse international setting and stakeholder variety, we were able to provide a comprehensive overview of factors to guide the development of antibiotic stewardship interventions.